Fair Trade market creation and marketing in the Global South. (December 2015) - Doherty, Bob; Smith, Alastair; Parker, Sara
Highlights: First empirical account of Global South Fair Trade market creation via four country cases. Propose a social forces framework of Fair Trade market creation in the Global South. Identify the contrast in marketing between the Global South and Northern Fair Trade markets. Contribute to theory of geographical entanglement by avoidance of geographical 'othering'. Marketing using imagined geographies with the collective aim of development, pride and dignity. Abstract: Fair Trade emerged to commercialise Southern products in the Global North on terms overtly beneficial to Southern producers. However, a contemporary phenomenon is the development of Fair Trade consumer markets within the Global South itself: and the paper explores this as a contribution to the evolving geographies of ethical consumerism. Data was captured from secondary sources and field visits that included in-depth interviews and participant observation. Analysis is informed by theories of market creation developed in economic geography and economic sociology. As such we focus on understanding (1) the architecture, or networks and institutions, of commercialisation, governance and certification and (2) the marketing practices and strategies, designed to resonate with and develop cognitive association amongst consumers. Given the alternative geographies of South–South vis-à-vis South–North Fair Trade, we deepen the geographical focus by applying frameworks emerging from the concept of 'geographical entanglement'. Findings identify the similarities and differences of both Southern Fair Trade market creation and marketing compared to the European experience. In some cases, the place-based 'othering', often used to develop sympathetic cognitive frames in Northern marketing, is identified, but this time operates around alternative geographical binaries. In other cases, we highlight instances that avoid such divisive place-making, and which instead draw on inclusive, rather than divisive, imagined geographies, overlaid with the collective aspiration for development, pride and dignity. These findings therefore inform the nature of geographical entanglement followed by ethical market creation, as well as contributing to the wider theoretical understanding of moral geographies endogenous to the Global South.